Is Work Time Control Good for Innovation? A Two-Stage Study to Verify the Mediating and Moderating Processes - Pan, Xiao; Zhao, Xiaokang; Shen, Huali (Frontiers in Psychology, 2022)
As part of job resources, work time control is essential for innovation. We examine how work time control impacts knowledge employees’ innovation in the workplace. A two-stage study was conducted to verify the mediating and moderating processes. In Study 1, adopting the job demands-resources model as a theoretical framework, we conduct a laboratory test to find the relation among work time control, job engagement, job burnout, and innovation and verify the path between work time control and innovation. In Study 2, drawing on the job demands-resources model verified by Study 1 and self-regulation theory, it is proposed that during the psychological process in the workplace, job engagement plays a mediating role and vocational delay of gratification plays a moderating role between work time control and innovation. 254 knowledge employees from diverse organizations participated in the survey study. After taking demographic variables, job demands, and neuroticism as control variables, the results show that job engagement would mediate the relationship between work time control and innovation. A higher level of delay of gratification buffered the effect of a higher level of work time control on innovation. All these findings verify and expand knowledge on work time control and innovation literature, showing that work time control is important for innovation. Based on Chinese cultural background, managers should offer employees the opportunity to conduct self-control training and encourage them with great freedom to foster employee innovation.